The Role of Dormitory Supervisors in Character Development of Children at Al-Falah Orphanage, Padang - Anshar, Sholeh; Sari, Putri Tiska; Ayashy, Diah Taubatry; Putra, Doli Aditia; Mardianto, Afri; Putra, Jefrison; Erlindawati, Erlindawati; Susi, Susi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Children are the next generation of the nation who must be educated, cared for, and given love, starting from the smallest scope such as family and community, as well as the nation and state. In the reality of social life, not all parents have the full capability and resources to meet the basic needs of children in order to achieve children's welfare. Poverty is the primary factor. This research aims to explore the character development of children at the Al-Falah Orphanage through religious guidance. The population in this study includes Dormitory Supervisors, the Head of Al-Falah Orphanage, with data sources collected through field observation, documentation, and interviews with the Head of Al-Falah Orphanage. Al-Falah Orphanage is a social organization that aims to assist orphans, new Muslims, and the underprivileged so that they have equal opportunities to achieve a brighter future. Al-Falah Orphanage is directly under the supervision of the Shine Al-Falah Foundation in Padang City.